IDENTIFICATION OF DROUGHT TOLERANT WHEAT GENOTYPES UNDER WATER DEFICIT CONDITIONS - Chachar, Zaid; Chachar, N. A.; Chachar, Q.I.; Mujtaba, S.M; Chachar, G.A; Chachar, Sadaruddin (International Journal of Research -GRANTHAALAYAH, 2016)
Climate change is emerging phenomena and causing frequent drought which lead to scaricity of water, which ultimately nagetively affecting wheat (Triticumaestivum L.) yield all around the world. The aim of this study was to explore the potential deought tolerant wheat genotypes for candidate genes exploration. This study was conducted during the year 2014-2015 at Plant Physiology Division, Nuclear Institute of Agriculture (NIA) Tandojam. The six wheat genotypes (cv. MT-1/13, MT-2/13, MT-3/13, MT-4/13 Chakwal-86 and Khirman) were investigated for their response at germination and seedling stage under different water stress treatments (0, -0.5, -0.75 and -1.0 MPa) in controlled conditions. The results of experiments with reference to genotypes revealed that genotype Chakwal-86 shows maximum seed germination (82.58 %), while the genotype Khirman shows maximum shoot length (7.23 cm), root length (15.1 cm), shoot fresh wt. (5.85 g 10-1shoots), root fresh wt. (3.45 g 10-1roots), shoot dry wt. (1.33 g 10-1shoots), root dry wt. (0.69 g 10-1roots). Among the genotypes tested Khirman and MT-4/13 are the tolerant genotypes had the potential to perform better under drought conditions, whereas MT-4/13 and Chakwal-86 were moderate tolerant under water stress conditions. Moreover, the genotypes i.e. MT-1/13 and MT-2/13 are the sensitive genotypes under drought environment. It is concluded from present in-vitro studies that osmotic stress significantly reduced the seed germination shoot/root length fresh and dry weight in all six wheat genotypes. The maximum reduction was found at higher osmotic stress induced by PEG-6000 (-1.0 MPa) significantly.